مقرر تعليم اللغة العربية للناطقين بغيرها : مدخل تقويمي(Muqarrar ta’lim al-lughat al-'Arabiyah li-al-natiqin bighayriha: madkhal taqwimi) - Osman, Nurulhuda (IIUM PRESS, 2009)
This book provides an introduction to evaluate syllabus of teaching Arabic for non-native speakers which is appropriate for the field of education and learning of this language in terms of linguistic, cultural, and educational content. The author discussed the general principles for the preparation of specifications in preparing a good syllabus for teaching Arabic for non-native speakers. She also had benefited from her own experience in teaching, and the experience of those experts in teaching Arabic languages in order to access the important and useful results towards development of teaching.